Current Concepts in Kidney Transplantation - Kapur, Sandip; Afaneh, Cheguevara; Aull, Meredith J. (IntechOpen, 2012)
Despite significant accomplishments to date, kidney transplantation is a relatively young field in medicine. Due to the armamentarium of agents available to effectively suppress the immune system, the past decade has seen a shift in focus from prevention of rejection to a focus on extending the life of the allograft and novel strategies to increase the organ donor pool. This book covers basic concepts in kidney transplantation while also addressing ways to manage kidney transplant recipients in order to maximize patient and graft survival. In addition, novel concepts to increase organ availability are addressed, including kidney paired donation and single site laparoendoscopic donor nephrectomy for living donor kidney transplantation, and utilization of marginal, hepatitis C positive, and older donor organs to increase deceased donor transplant opportunities.